2021
DOI: 10.1590/s1808-185120212002240563
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Spinal cord Injury in references trauma center in Curitiba (Paraná, Brazil)

Abstract: Objective: To outline the clinical-epidemiological profile of patients who were victims of SCT, to identify the main trauma mechanisms for this injury and its outcome. Methods: Retrospective cross-sectional study, in which the epidemiological data, computed tomography reports and medical records of patients with fractures identified in their examinations at trauma reference hospitals in Curitiba-PR, in 2018, were analyzed. Results: 705 patients were studied. There was a male prevalence (64%), the most affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…3 The epidemiological data from Curitiba show that patients with spinal cord injuries are more prevalent in young men aged 45 years, victims of traffic accidents. 4 A previous study in the United States showed that the estimated annual incidence of spinal cord injury was approximately 12,000 new cases in 2011, and the estimated number of people living with neurological sequelae is 232,000 to 316,000. 5 From the local perspective in the city of Curitiba, the previous epidemiological studies are concentrated in the early 2000s, with a need for a recent review, given the implementation of the whole--body tomography study in polytrauma patients who are seen in the emergency department, as well as the expansion and improvement of pre-hospital care.…”
Section: Introductionmentioning
confidence: 99%
“…3 The epidemiological data from Curitiba show that patients with spinal cord injuries are more prevalent in young men aged 45 years, victims of traffic accidents. 4 A previous study in the United States showed that the estimated annual incidence of spinal cord injury was approximately 12,000 new cases in 2011, and the estimated number of people living with neurological sequelae is 232,000 to 316,000. 5 From the local perspective in the city of Curitiba, the previous epidemiological studies are concentrated in the early 2000s, with a need for a recent review, given the implementation of the whole--body tomography study in polytrauma patients who are seen in the emergency department, as well as the expansion and improvement of pre-hospital care.…”
Section: Introductionmentioning
confidence: 99%